"We learned how to live in Pallanza" - John T. LEHMAN (Journal of Limnology, 2000)
After months of paralysis from injuries sustained in an automobile accident, W. Thomas Edmondson died in Seattle during January. Known as "Tommy" to one and all, in keeping with his nickname he retained a youthful and alert mind until the end. Tommy Edmondson will remain forever linked with the field of limnology that he loved. It is easy to recount his growth and accomplishments in science, starting from his first glimpse of a rotifer through the microscope he received as a gift at the age of 12. Those fortunate to have visited with him in his Seattle office can recall fondly the sight of a desk and chair piled high with "study graphs" and various works in progress which he would graciously set aside in welcome and eager interest for the visitor. But by his own reckoning, Tommy declared that there was a moment in time that was transformational in spirit and mind. That was the period in 1959 and 1960 during which he took sabbatical leave at the great limnological centers in Windermere, Uppsala, and Pallanza. Thirty five years later, he recalled the events with earnest delight, but his fondest memories were reserved for the town on the shore of Lago Maggiore. "We learned how to live in Pallanza," was his assessment of the time.